Development of Learning Evaluation Instruments to Measure Creative Thinking Skills in The Reproductive System Concept - Mulyaningsih, Yeni; Sukmawardani, Yulia; Farida, Ida; Nuryantini, Ade Yeti; Hamidah, Nur (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2024)
The passage highlights the significance of creative thinking skills as an essential component of 21st-century education, alongside critical thinking, collaboration, and communication skills, collectively known as the 4Cs. The research aims to develop evaluation instruments to enhance students' creative thinking skills in reproductive system material. This topic involves contextual health content, requiring creative thinking to address it. The four indicators for creative thinking skills include fluency, flexibility, originality, and elaboration. The research and development (R&D) method is employed in this developmental study. The passage describes the process of creating 10 questions based on curriculum achievements, followed by validation by experts and a final stage of testing the questions on 40 ninth-grade science students at MAN 2 of Bandung. The results indicate that one question was accepted without revisions, six questions were accepted with revisions, and three questions were rejected. The reliability of the questions reached a score of 0.73, categorized as high, meaning the questions consistently provided similar measurement results. The students' answers to the evaluation questions require creative thinking skills, indicating that these questions effectively train those skills.